Linkage Islamicity Performance Index and Islamic Corporate Governance throught Financial Health Performance of Indonesian Islamic Banks - Prihantono; Sukardi, Budi; Riyani; Kurniati , Pratiwi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study examines the impact of the Sharia Supervisory Board's size (SSB) and the Board of Directors on the financial performance of Islamic commercial banks in Indonesia, focusing on a decade-long period from 2011 to 2020. The research adopts a quantitative approach, analyzing secondary data from the Good Corporate Governance (GCG) reports of ten selected Sharia Commercial Banks (BUS). Advanced panel data analysis techniques, including regression model estimation, model selection, assumption testing, and hypothesis testing, are utilized to ensure a robust examination. The analysis reveals multifaceted outcomes. Key financial indicators such as the profit-sharing ratio, zakat performance ratio, and Islamic income ratio show no significant impact on the bank's financial health. However, the Islamic investment ratio positively correlates with financial robustness. The size of the SSB has a negative, albeit insignificant, influence, whereas the Board of Directors' size does not significantly affect financial health. Notably, the study highlights the substantial moderating effects of SSB and the Board of Directors on the relationship between the Islamicity performance index and financial health. This research contributes to the field by showcasing the critical roles of SSB size and the Board of Directors in evaluating the financial health of Islamic commercial banks. It provides practice and theory implications of the factors that drive financial performance, offering valuable insights for policymakers and stakeholders in the Islamic banking sector.